Sweet potato and wild relatives - Molecular data - Rodriguez, P; Scotland, R (University of Oxford, 2018)
This dataset includes all the molecular data generated as part of a project to study the origin and evolution of the sweet potato. The dataset consists of three types of DNA sequences generated through high-throughput sequencing: whole chloroplast genomes, single-copy nuclear coding regions, and the non-coding ribosomal Internal Transcribed Spacer (ITS). In terms of taxon sampling, this dataset includes multiple specimens of sweet potato and its fifteen closest wild relatives, as well as twenty other species of morning glories. This dataset was generated as part of a comprehensive phylogenetic study of all species closely related to sweet potato that addressed several questions pertaining to the origin and evolution of the crop.